MCF-7 Resistant Doxorubicin are Characterized by Lamelapodia, Strong Adhesion on Substrate and P-gp Overexpression - Dyaningtyas Dewi Pamungkas Putri; Sarmoko Sarmoko; Rifki Febriansah; Endah Puspitasari; Nur Ismiyati; Aditya Fitriasari (Indonesian Journal of Cancer Chemoprevention, 2011)
The prognosis of breast cancer patients is closely associated with the response of tumor cells to chemotherapy agent. Doxorubicin is one of the primary chemotherapeutic agents used for the treatment of breast cancer. Resistance to chemotherapy is believed to cause treatment failure in cancer patients. Furthermore, long time exposure to chemotherapeutic agent induces cancer cells resistance. MCF-7 sensitive cells used as chemoresistance model have overexpression P-gp (P-glycoprotein). Chemoresistance was established by treating MCF-7 cells with 0.5 µg/ml doxorubicin-contained medium for a week. 50% inhibiting concentration (IC50) doxorubicin on MCF-7 cells/DOX were determined using MTT assay. Western blot assay and immunocytochemistry assay was performed to determine the expression of P-gp. Morphological of MCF-7 cell/DOX was changing to become larger and have lamellapodia. IC50 value of doxorubicin was 700 nM on MCF-7/DOX and 400 nM on sensitive MCF-7 cells. The MCF-7/DOX sensitivity to doxorubicin was decreased, shown by 1.5 fold higher IC50 of doxorubicin on MCF-7/DOX compared to MCF-7 sensitive cells. Treatment doxorubicin to sensitive MCF-7 cells leads to the increasing P-gp expression. The P-gp level expression has strong correlation with the low sensitivity of MCF-7/DOX to doxorubicin.Keywords: doxorubicin, resistance cells, sensitive MCF-7 cell